Kedudukan Mazhab Syafi'i dalam Perkembangan Ahlus Sunnah di Negeri Perlis - Man, Saadan (Jurnal Fiqh, 2007)
Perlis is known as the only state in Malaysia which declares itself as not bound to adhere to the Shafi`ite madhhab in practising Islamic law. This is a result of Islamic reformism, better known in Perlis as Ahlus Sunnah, which is fairly dominant in the state. In spite of this fact, one might see so many Islamic practices done by local Muslims which are regularly associated to the Shafi'ite madhhab. This proves that the influence of Shafi'ite madhhab is still prevalent in the state. This article shall examine to what extent the madhhab survives in the rapid growth of Islamic reformism in Perlis Muslim society.